Loss‐of‐function mutations in ISCA2 disrupt 4Fe–4S cluster machinery and cause a fatal leukodystrophy with hyperglycinemia and mtDNA depletion. Issue 4 (22nd January 2018) - Alaimo, Joseph T.; Besse, Arnaud; Alston, Charlotte L.; Pang, Ki; Appadurai, Vivek; Samanta, Monisha; Smpokou, Patroula; McFarland, Robert; Taylor, Robert W.; Bonnen, Penelope E.
Abstract: Iron–sulfur (Fe–S) clusters are essential cofactors for proteins that participate in fundamental cellular processes including metabolism, DNA replication and repair, transcriptional regulation, and the mitochondrial electron transport chain (ETC). ISCA2 plays a role in the biogenesis of Fe–S clusters and a recent report described subjects displaying infantile‐onset leukodystrophy due to bi‐allelic mutation of ISCA2 . We present two additional unrelated cases, and provide a more complete clinical description that includes hyperglycinemia, leukodystrophy of the brainstem with longitudinally extensive spinal cord involvement, and mtDNA deficiency. Additionally, we characterize the role of ISCA2 in mitochondrial bioenergetics and Fe–S cluster assembly using subject cells and ISCA2 cellular knockdown models. Loss of ISCA2 diminished mitochondrial membrane potential, the mitochondrial network, basal and maximal respiration, ATP production, and activity of ETC complexes II and IV. We specifically tested the impact of loss of ISCA2 on 2Fe–2S proteins versus 4Fe–4S proteins and observed deficits in the functioning of 4Fe–4S but not 2Fe–2S proteins. Together these data indicate loss of ISCA2 impaired function of 4Fe–4S proteins resulting in a fatal encephalopathy accompanied by a relatively unusual combination of features including mtDNA depletion alongside complex II deficiency and hyperglycinemia that may facilitate diagnosis of ISCA2 deficiency patients. Abstract : ISCA2 loss of function in humans causes fatal encephalopathy with hyperglycinemia, leukodystrophy of the brainstem with longitudinally extensive spinal cord involvement, and mtDNA deficiency. In vitro studies demonstrated that loss of ISCA2 impairs respiration, ATP production, and mitochondrial membrane potential, as well as diminished mtDNA copy number. Loss of ISCA2 compromised the function of ETC complex II and protein lipoylation which are dependent on 4Fe‐4S proteins but did not disrupt 2Fe‐2S protein dependent proteins ABAT and UQCRC.